CHARACTERISTIC OF HYDATIDIFORM MOLE PATIENTS IN PATHOLOGY ANATOMY LABORATORY HASANUDDIN UNIVERSITY - Rina Masadah (Nusantara Medical Science Journal, 2016)
ABSTRACT Background: Hydatidiform Mole (complete and partial) is one of Gestational Trophoblastic Diseases (GTD) characterized by the occurrences of trophoblastic cell proliferation and abnormal placenta flakes. It can develop into malignancy, metastasis, and cause death. Therefore, characteristic data of the patients in applying preventive program and optimal therapy are required. This research evaluates the frequency and distribution of the hydatidosa mole patients and its type in the annual period from 2012 to 2015 and several responsible risk factors, such as age and obstetric history of the patients. Methods: reviews of histopatology specimen of hydatidiform mole were conducted as many as 255 cases which met the inclusion criteria in the period of January 2012 to September 2015. The review particularly determines the histopathology diagnosis of hydatidiform mole and its type. Results: The number of hydatidiform mole patients in the period of January 2012 to September 2015 is 255 patients. Approximately 70.65% cases of those are categorized as completed hydatidiform mole. The highest frequency of mole occurs in the range of ages from 21 to 25 years old (24.19%). About 28.57% cases occur on the first pregnancy and 7 out of 255 are recurrent case of mole pregnancy. Conclusions: The occurrences of hydatidiform mole found in Pathology Anatomy Laboratory of Medical Faculty of Hasanuddin University are quite high, and the cases of completed hydatidiform mole are in the highest number. The numerous patients of hydatidiform mole are commonly found in the youngster group and low gravidity.  Keywords: gestational trophoblastic disease, hydatidiform mole